2014
DOI: 10.7567/jjap.53.06jh01
|View full text |Cite
|
Sign up to set email alerts
|

Through silicon via filling methods with metal/polymer composite for three-dimensional LSI

Abstract: The novel use of metal/polymer composite can be a new candidate for filling through silicon vias (TSV) for three-dimensional (3D) LSI, as it provides a much faster and inexpensive fabrication process compared to copper electroplating. In this study, different process methods have been tested in order to optimize TSV filling with Ag/polypyrrole composite. All together nine method set-ups have been examined to analyse their average filling ratios. The statistical analysis of the techniques showed that the maskin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…However, there are problems of shrinkage or partial filling and polymer may degrade over time. [25,26] Recently, SiC-based and Bi-Sn-Ag solders have been tested for the TSV filling. However, extrusion properties are not discussed.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are problems of shrinkage or partial filling and polymer may degrade over time. [25,26] Recently, SiC-based and Bi-Sn-Ag solders have been tested for the TSV filling. However, extrusion properties are not discussed.…”
Section: Introductionmentioning
confidence: 99%
“…The key performance of TSVs is determined by the filling materials used in the silicon via. There are various materials that have been used for the TSV, such as tungsten (W), copper (CU) [28,29] and a Ag/polypyrrole composites [30]. The copper is the most commonly used filling material for TSV due to its excellent electrical conductivity and low process costs.…”
Section: Cnt-based Interconnectsmentioning
confidence: 99%
“…For example, Lin et al demonstrated the vacuum filling of complex microchannels with liquid metal [7]. Unfortunately, these two methods require a pressure vessel and additional work such as pressurization and depressurization [8][9][10]. Thus, more efficient methods are required.…”
Section: Introductionmentioning
confidence: 99%